Remote Sensing and Mycorrhizal-Assisted Phytoremediation for the Management of Mining Waste: Opportunities and Challenges to Raw Materials Supply - Castagno Gañán, Ana Rosa (2023)
In recent times, the development of innovative processes permits the application of a circular economy approach to the management and exploitation of mining waste with respect to human health and environment, such that society is changing its fundamentally negative perception of the mining sector. This study presents the opportunities and challenges of supplying raw materials from waste using a remote sensing technique, mycorrhizal-assisted phytoremediation, and hydrometallurgical techniques to transform mining waste from a problem to a resource. Soil/mine wastes from the Sierra Pintada mine (Mendoza, Argentina) were mineralogically and chemically analyzed, and then, a mapping of the mining waste was carried out by Sentinel-2A images to identify areas with similar characteristics. The bioaccumulation of HMs by autochthonous shrubs was also determined to select accumulator plant species, and to evaluate their potential for phytoremediation of mine soils at different technological scales, when they were inoculated with arbuscular mycorrhizal fungi originated from a mining-impacted area. RMs were recovered from plant biomass by scaling in bioreactors, the depuration module, and hydrometallurgical techniques. The encouraging results highlight that this multidisciplinary approach can be applied to meet the increasing demand for RMs supply and, at the same time, to protect the environment and public health.